Neural network training to support decision making ON FOREX MARKET - V. A. Rybak; H. M. Sulaiman (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki)
The analysis confirmed the relevance of the application of neural networks for decision support in the Forex. Designed algorithm for creating trading signals and selected indicators will determine how the formation of the training sample. The step of selecting the neural network structure and its training will be described in subsequent publications.